Helium ion microscope generated nitrogen-vacancy centres in type Ib diamond - Donegan, John; Cross, Graham; Zhang, Hongzhou; Mc Closkey, David (My University, 2014)
We report on position and density control of nitrogen-vacancy (NV) centres created in type Ib diamond using localised exposure from a helium ion microscope and subsequent annealing. Spatial control to <380 nm has been achieved. We show that the fluorescence lifetime of the created centres decreases with increasing ion dose. Furthermore, we show that for doses >1 × 1017 ion/cm2, significant damage of the diamond lattice occurs resulting in fluorescence quenching and amorphization. This places an upper limit on the density of NV centres that can be created using this method.
PUBLISHED
Cited by 1
Keywords: Photoluminescence; Ion radiation effects; Vacancies; Fluorescence; Diamond